Design of Reservoirs Enabling Stress-Induced Sequential Release Systems - Osamah Altabal; Christian Wischke; Andreas Lendlein (MDPI AG, 2022)
Mechanical stress is recognized as a principle for opening enclosed compartments through compression, stretching, or shear, eventually resulting in the onset of a diffusion-controlled release. Here, we hypothesized that the geometrical design of cavities (cut-outs) introduced as containers in elastic polymer substrates and sealed with a brittle coating layer would enable a pre-defined release of different compounds by stress concentration phenomena. Design criteria such as cut-out shapes, orientations, and depths were initially assessed for suitably different stress concentrations in computational models. In substrates fabricated from polydimethylsiloxane by photolithographic techniques, the local strains at horizontal rectangular, circular, and vertical rhombus-shaped cut-outs systematically increased under horizontal stretching as proposed. When filled with model compounds and coated with poly(n-butyl cyanoacrylate), a pre-defined induced breakage of the coating and compound release was confirmed upon continuous uniaxial stretching. This proof of concept demonstrates how device design and functions interlink and may motivate further exploration in technology and medicine for deformation-induced on-demand dosage applications.